Altered Humoral Immune Responses and IgG Subtypes in NOX2-Deficient Mice and Patients: A Key Role for NOX2 in Antigen-Presenting Cells - Cachat, Julien; Deffert, Christine; Alessandrini, Marco; Roux-Lombard, Pascale; Le Gouellec, Audrey; Stasia, Marie-José; Hugues, Stéphanie; Krause, Karl-Heinz (Frontiers in Immunology, 2018)
Chronic granulomatous disease (CDG) is a primary immunodeficiency resulting from loss of function mutations in the reactive oxygen species generating phagocyte NADPH oxidase (NOX2). CGD patients are prone to infection, but also have an increased susceptibility to autoimmune diseases. The aim of this study was to investigate the role of NOX2 in the regulation of specific immunity. In both CGD patients and NOX2-deficient mice, we observed an alteration in the basal proportions of IgG subtypes. Upon immunization with curdlan -a dectin 1 agonist- NOX2-deficient mice showed increased production of IgG2c compared to controls, and re-stimulation of lymph node-derived cells led to increased production of IFN, but not IL-5, indicative hallmark of an enhanced Th1 response. T cell activation was increased in NOX2-deficient mice and a similar trend was observed in vitro when T cells were co-cultured with NOX2-deficient bone marrow derived cells. In contrast, no difference in T cell activation was observed when NOX2-deficient T cells were co-cultured with wild-type BMDC. Following stimulation of NOX2-deficient dendritic cells, no difference in costimulatory molecules was observed, while there was an increase in the release of Th1-driving cytokines. In summary, both CGD patients and CGD mice have an altered IgG subtype distribution, which is associated with an increased IFN production. Thus, NOX2 within dendritic cells appears to be an important regulator at the interface of innate and specific immunity, especially after activation of the dectin 1 pathway, limiting immune activation and the development of autoimmunity.